INTERNALISASI KARAKTER ULUL ALBAB DALAM PEMBELAJARAN AKUNTANSI BERBASIS PROJECT BASED LEARNING - Kholilah Kholilah; Ayub Wijayati Sapta Pradana; Ahmad Djalaluddin; Dyah Febriantina Istiqomah (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2021)
This study was designed to find out the meaning of financial accounting learning that integrates the character of ulul albab with project-based learning. The learning model is carried out through the implementation of projects that allow students to practice accounting for SMEs. This research fills the void of discussion about learning models that integrate science and Islam in the field of accounting. The study was conducted in Financial Accounting class for S1 accounting class of 2017 students at UIN Malang. This study used a quasi-experimental study to examine differences in accounting scores in the project class and the control class—different test using paired sample t-test. The results showed that there were differences in accounting values in the experimental class before and after project. Score differences also occur between the experimental class and the control class. Internalization of ulul albab's character is obtained through students' responses to problems that occur during the project. The limitation of the study is the construct of the ulul albab character which has not been measured so that it cannot be done to test different internalization of the ulul albab character in the experimental class and the control class.